2015
DOI: 10.1016/j.recot.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Estudio prospectivo aleatorizado sobre la influencia del bloqueo distal del clavo Gamma 3 en el tratamiento de las fracturas pertrocantéreas de fémur

Abstract: ResumenObjetivo: El propósito de este estudio es valorar la necesidad de bloquear distalmente los clavos Gamma 3 (Stryker. Mahwah, New Jersey. USA) en fracturas pertrocantéreas de fémur 31-A1 y 31-A2 de la AO. Material y métodos: Desde junio de 2011 hasta enero de 2013 se recoge una muestra formada por 177 pacientes con fractura pertrocantérea de fémur tratados en nuestro centro mediante osteosíntesis con clavo Gamma 3 estándar. Es un estudio prospectivo y aleatorizado según el año de nacimiento de cada pacien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 15 publications
(25 reference statements)
2
16
0
Order By: Relevance
“…Other 10 unrelated biomechanical studies were excluded after further reading. Finally, only 9 studies (4 randomized controlled trials [12][13][14][15] and 5 observation studies [16][17][18][19][20]) met our inclusion and exclusion criteria, including 7 in English [12][13][14][16][17][18][19], 1 in Spanish [15] and 1 in Korean [20] (Fig. 1).…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Other 10 unrelated biomechanical studies were excluded after further reading. Finally, only 9 studies (4 randomized controlled trials [12][13][14][15] and 5 observation studies [16][17][18][19][20]) met our inclusion and exclusion criteria, including 7 in English [12][13][14][16][17][18][19], 1 in Spanish [15] and 1 in Korean [20] (Fig. 1).…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Among the included randomized controlled trials, all of them [12][13][14][15] reported an adequate generation of the allocation sequence and concealment, but surgeons blinded to the surgical intervention were not present in their design study. In all these studies the evaluation process of the outcome was also not blinded.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations